Depresi Dalam Perspektif Al-Qur’an (Studi Tafsir Tematik) - Sovia Vega Savela; Mayrina Eka Prasetyo Budi (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo Indonesia, 2024)
Abstract: Nowadays, depressive mental health disorders that occur in society are always viewed from a medical or psychological perspective only. From an Islamic perspective, the Al-Qur’an also looks at the problem of depression and this can be studied from the perspective of the Al-Qur’an. Therefore, this research tries to find out what the terminology of depression is in the Al-Qur’an, what the verses about depression are in the Al-Qur’an and what solutions the Al-Qur’an offers to prevent depression. This study used qualitative research methods. The type of research used in this research is library research. The data sources in this research are divided into two, namely primary data sources and secondary data sources. Primary data sources are verses from the Al-Qur’an, while secondary data sources are books, books and articles. This research collects and analyzes data using a thematic or maudhu'i approach, namely collecting verses from the Al-Qur’an with certain topics or titles with one overall theme. The results obtained from this research show that there are four terms in the Al-Qur’an that represent the meaning of depression, namely the words khauf, ya'us, khassyah and qanuth. Depressive verses in the Qur'an include Q.S Al-Baqarah [2]: 155, Q.S Al-Maidah [5]: 52, Q.S Yusuf [12]: 87, and Q.S Al-Hijr [15]: 56 . The Qur’an offers a solution to preventing depression, namely by being patient in Q.S Al-Baqarah [2]: 155, increasing faith in Q.S. At-Taubah [9]: 40, endeavor and trust in Q.S. At-Taubah [9]: 51 then gratefully in Q.S Al-Hijr [15]: 88. Keywords: Depression, Mental Health, Thematic Interpretation, Al-Qur'an.